Late Presentation, Advanced Disease and Severe Acute Malnutrition are Common Among Children with Cancer in Tanzania (Tanzania Medical Journal, 2021)
BackgroundMajority of children with cancer live in low and middle-income countries (LMIC) where survival is disproportionately low compared to high-income countries (HIC). Among the challenges of managing childhood cancers in LMIC is late presentation, advanced disease, and the prevalence of severe malnutrition. Advanced disease and severe acute malnutrition are associated with poor treatment outcomes. Methodology This was a descriptive study conducted in Tanzania at Ocean Road Cancer Institute (ORCI) in 2010. Children and adolescents below 18 years were longitudinally enrolled in the study. Pathological diagnosis was made by examination of tissue biopsies, fine needle aspiration (FNAC) or bone marrow aspiration cytology (BMAC).  Stage of disease at presentation was determined by physical examination and radiological investigations such as chest x-ray and ultrasonography. World Health Organization (WHO) anthropometric measurement chart was used to interpret measured Mid-upper arm circumference (MUAC) for age. Body mass index (BMI) is affected by tumour weight hence was not used to assess malnutrition in this study. Results One hundred and fifty-one (151) patients were enrolled in the study. The mean age at presentation was 5.8 years (range 3-17years), and 51.7% of participants were males. Three quarters (76.6%) of patients attended the first health facility within a month of onset of symptoms, but forty per cent (40%) of patients took six (6) months to reach ORCI for treatment. Eighty-six percent (86%) of patients presented with advanced disease (50.8% - locally advanced, 35.1% - metastatic disease). Metastatic disease was more frequent in patients with Neuroblastoma (NB) and Non Hodgikins Lymphoma (NHL) (66.6% each), Burkitt’s lymphoma (BL) (50%), Soft tissue sarcoma (STS) (40%) and Wilm’s tumour (WT) (35.3%). Severe wasting was seen in 12.6% of patients, and more prevalent among patients with BL (31.3%) and WT (25%).ConclusionEven though most patients sought health care early, they reached ORCI late with advanced disease (86%), and 12.6% had severe acute malnutrition.Keywords: Children, Cancer, Advanced Disease, Malnutrition.